Evaluasi Dampak Penggunaan Teknologi Pada Prestasi Academik Siswa: Studi Berbasis Data Sekunder - Laia, Afrian; Hia, Jeksen Bahtera (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research aims to examine the impact of technology use on student academic achievement through secondary data analysis. This study utilizes data from various educational institutions in Indonesia covering the 2019-2023 period and involving 1,500 high school students. The methodology applied is quantitative analysis of existing datasets, with a focus on the relationship between technology use pattern and academic achievement indicators. The result showed a significant positive correlation (r = 0.68, p < 0.01) between the use of technology for educational purposes and academic achievement, especially in STEM subjects. However, excessive use of technology for non-educational purposes showed a negative correlation (r = -0.45, p < 0.01) with academic performance. This research concludes that although educational technology can improve student student achievement, appropriate guidance and restrictions on use remain essential to achieving optimal results. These findings provide useful insights for educational institutions in formulating technology integration policies.